Genitourinary cancers in the Arab world: A bibliometric study - Ibrahim, Sarah; Farhat, Theresa; Baalbaki, Rim; Aoun, Michael; Toumieh, Georgio; Kaddoura, Malak; Jaber, Lubna; Taher, Ali T.; Abdul-Sater, Zahi (Frontiers in Urology, 2022)
Background The genitourinary cancer burden in the Arab region is rising at an increasing pace. The main objective of this study was to conduct a bibliometric analysis of scientific publications on genitourinary cancer to understand the growth, impact, trends, and flow of knowledge within GU cancer research in 22 Arab countries. Methods The Web of Science databases were searched for publications related to genitourinary cancer research in the 22 Arab countries from January 1, 2002, till December 31, 2021. The scientific research was evaluated based on productivity (number of published documents, authorships), impact (citation counts and journals impact factor), collaborations, and areas of interest for published papers. Results A total of 3,129 papers met the inclusion criteria in this research. After adjusting for the population power, Qatar (53.57) and Lebanon (46.83), Saudi Arabia (46.21), Jordan (41.58), and Tunisia (40.72) had the highest research productivity. The number of articles and average citations per year was generally increasing. Most Arab corresponding authors were from Egypt, Saudi Arabia, and Tunisia, and most Arab first authors were male researchers, highlighting gender inequality in genitourinary cancer research. Both regional and international collaborations are weak between authors in the field. Conclusion This bibliometric research provided a framework for visual and quantitative research productivity on GU can in the Arab world. Research output is low in some countries, which can be improved by investing in more international and national collaborative research projects in the field of GU cancer.